Hubungan dan Aliran Informasi Antar Pelaku pada Klaster Batik Kota Pekalongan - Dwi Astuti; Jawoto Sih Setyono (Jurnal Wilayah dan Lingkungan, 2016)
Batik Pekalongan potentially has a unique characteristic developed by each entrepreneur. The relationships between entrepreneurs in order to stimulate the innovative development of batik should be examined for future development. This study aims to determine how the relationships between and information flow across the actors involved in cooperation networks to support batik cluster development in Pekalongan. The research conducts survey method with both qualitative and quantitative approaches. The data is obtained from primary and secondary data. This study aims to understand the relationships between the actors involved in the batik cluster through Social Network Analysis (SNA). The results show that the roles of actors are still not optimal and need to be improved. Disperindagkop and UMKM, Bappeda, Ministry of Industry, and FEDEP BPPT of Pekalongan City have the major role in developing batik clusters. Their contributions are measured from techniques of centrality degree, closeness centrality, and betweenness centrality in the network. The source of batik knowledge information source comes from the both the customers and the entrepreneurs of batik. The sources of batik knowledge sharing come from the consumers useful to information exchange and innovation sharing which affect to batik production process. Batik cluster consists of multi-stakeholders carrying out some shortcomings so that it is necessary to integrate the roles of actors and the innovation process and technology as a strategy for the development of innovative clusters.